Konsep Implementasi Kurikulum Pendidikan Tinggi di Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto: Integrasi fluid-intelligence dan crystallized-intelligence - Sukarno (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
The purpose of this research is to describe the concept of implementation of the higher education curriculum at the Tarbiyah Raden Wijaya Mojokerto College of Sciences which integrates fluid-intelligence and crystallized-intelligence. This research is a qualitative participatory study, the research design is a reflexive process that operates through each stage of the activity of collecting and analyzing data. Data is collected using literature study techniques and documentation studies, then analyzed by systematic cross-case comparisons from a number of case studies. From the results of the discussion it can be concluded as follows: 1) Adult students rarely participate in campus social activities or services, often outside the group model with little interaction in efforts such as group projects, and experiential orientation programs or socialization courses that are rarely given work and family demands . 2) The curriculum of the Tarbiyah Raden Wijaya School of Science is built based on students' learning abilities integratively by prioritizing fluid intelligence content in the initial and mid semeter which is gradually derived which leads to crystallized intelligence content, thus making students in addition to having high intellectuals are also strong in working in their profession.